Non-elite Women Candidate and Middle Pathway in Indonesia's 2024 Local Election - Harahap, Raegen; Anisyah, Siti; Sattar, Yasmin (Universitas Muhammadiyah Malang, 2025)
In Southeast Asia, women's political representation is often explained through dynastic ties or grassroots activism. This article examines non-elite women candidates in the 2024 Legislative Election in Ogan Ilir, Indonesia, using Choi's